PELATIHAN PUBLIC SPEAKING DAN LITERASI HUKUM KOMUNIKASI DALAM MEMBANGUN SELF CONFIDENCE PELAJAR EFL DALAM INTERAKSI SEHARI-HARI - Afriana, Afriana; Arianto , Tomi; Jamba , Padrisan (PUAN INDONESIA, 2024)
The ability to speak English is one of the skills that students must have as a skill that can be used in the workforce. In the world of work, students who have graduated are required to have skills in communicating in English, and discussing communication, students are also expected to understand communication literacy. Many are good at speaking English but sometimes lack direction and lack knowledge about communication literacy. On this occasion, Putera Batam University lecturers held training for Putra Jaya Vocational School students. This training uses a lecture method combined with a question and answer session. This training is delivered directly by lecturers who are experts in their fields, namely English Literature and Legal Studies. This training is very important because some companies set English language standards because the ability to communicate using English is important for students' careers and students must have this ability to be able to survive in the midst of competition. Apart from that, you must be wise and clever in communication literacy. The results obtained from this service found that many students lacked confidence when asked to speak in front and did not understand legal literacy. After the service was carried out, it could be seen that students showed the need for practice in building self-confidence and students' understanding of legal literacy.